Factors Associated With Early Elementary Child Health-Related Quality of Life: The Generation R Study - You, Yueyue; van Grieken, Amy; Estévez-López, Fernando; Yang-Huang, Junwen; Raat, Hein (Frontiers in Public Health, 2022)
Aim: To identify the factors associated with health-related quality of life (HRQOL) among early elementary age children (5-6 years) from a general population sample. Methods: We analyzed data of 4,202 children from the Generation R Study, a population-based cohort study in the Netherlands. Children’s physical and psychosocial HRQOL were measured using the Child Health Questionnaire Parent Form 28 (CHQ-PF28). Associations between socio-demographic characteristics (child age, sex, ethnic background, family situation, parental educational level, parental employment status, and net household income), health-related lifestyle behaviors (physical activity and screen time), health conditions (number of chronic conditions, emotional and behavioral problems, and family functioning) and children’s physical and psychosocial HRQOL were assessed using multivariate regression analyses. Results: Mean child age was 6.0 years (SD: 0.43); 63.6% had a majority (Dutch) ethnic background. Children with a non-western ethnic background, and children of unemployed mothers had a lower physical HRQOL (all p<0.05). Older children, boys, and children from single-parent or low educated families had a lower psychosocial HRQOL (all p<0.05). Children from a low income household family, children having chronic conditions or emotional and behavioral problems, or from families with relatively high ‘pathological family functioning’ reported both lower physical and psychosocial HRQOL (all p<0.05). Conclusion: Indicators of adverse socioeconomic and family circumstances and indicators of child health problems were associated with lower HRQOL. Public health initiatives to improve HRQOL of children should prioritize children from a low socioeconomic status or with less favorable health conditions from early age onwards. Keywords: socio-demographic characteristics; socioeconomic status; health-related lifestyle behaviors; chronic conditions; HRQOL; early elementary school age children.